The association between in-utero exposure to stressful life events during pregnancy and male reproductive function in a cohort of 20-year-old offspring: The Raine Study. Issue 7 (30th May 2019) - Bräuner, E V; Hansen, Å M; Doherty, D A; Dickinson, J E; Handelsman, D J; Hickey, M; Skakkebæk, N E; Juul, A; Hart, R
Abstract: STUDY QUESTION: Is exposure to gestational stress in the critical time window for the normal differentiation and growth of male reproductive tissue associated with male reproductive function in offspring in later life? SUMMARY ANSWER: Exposure to stressful life events (SLEs) in early, but not late gestation, are associated with reduced adult male reproductive function, consistent with the hypothesis that events during early prenatal life programme adult male reproductive function. WHAT IS ALREADY KNOWN: Animal studies suggest that gestational stress may impact on the reproductive function of male offspring, but human evidence is sparse. STUDY DESIGN, SIZE, DURATION: Using a prospective longitudinal cohort, we examined the association between number and type of maternal stressors during pregnancy in both early and late gestation and reproductive function in 643 male Generation 2 (offspring) at age 20 years. Mothers and their male Generation 2 (offspring) from The Raine Study participated. Mothers prospectively reported SLEs during pregnancy recorded at gestational weeks 18 and 34 using a standardized 10-point questionnaire. PARTICIPANTS/MATERIALS, SETTING, METHODS: The 643 male Generation 2 (offspring) underwent testicular ultrasound examination and semen analysis and provided serum for reproductive hormone analysis. Multivariate linear regression analysis was used to examine associations. MAIN RESULTS AND ROLE OF CHANCE: Of 643 recruited males, 407 (63%) were exposed to at least one SLE in early gestation. Fewer SLEs were reported in late gestation ( n  = 343, 53%). Maternal SLE exposure in early gestation was negatively associated with total sperm count (β = −0.31, 95% CI −0.58; −0.03), number of progressive motile sperm (β = −0.15, 95% CI −0.31; 0.00) and morning serum testosterone concentration (β = −0.04, 95% CI −0.09; −0.00). No similar effects of maternal SLE exposure in late pregnancy were detected. The large sample size and an objective detailed direct assessment of adult male reproductive function with strict external quality control for sperm quality, as well as detailed prospectively collected information on prenatal SLEs in two distinct time windows of pregnancy reported by the women in early and late gestation along with other risk factors, imply minimal possibility of recall, information bias and selection bias. When assessing our results, we adjusted for a priori chosen confounders, but residual confounding or confounding by factors unbeknown to us cannot be ruled out. LIMITATIONS, REASONS FOR CAUTION: It is not possible to measure how SLEs impacted differently on the mother's experience or perception of stress. Resilience (coping) gradients may alter cortisol levels and thus modify the associations we observed and the mothers' own perception of stress severity may have provided a more precise estimate of her exposure. WIDER IMPLICATIONS OF THE FINDINGS: Our findings suggest that exposure to SLEs in early, but not late gestation, are associated with reduced adult male reproductive function. Improved support for women with exposure to SLEs during pregnancy, particularly during the first trimester, may improve the reproductive health of their male offspring in later life. Intervention studies of improved pregnancy support could provide more insight into this association and more information is needed about the potential specific epigenetic mechanisms underlying this association. STUDY FUNDING/COMPETING INTEREST(S): The male fertility sub-study was funded by NHMRC Grant 634 457. The core management of the Raine Study is funded by University of Western Australia, Curtin University, Telethon Kids Institute, Women and Infants Research Foundation, Edith Cowan University, Murdoch University, The University of Notre Dame Australia and Raine Medical Research foundation. Dr Bräuner's salary was supported by Læge Sofus Carl Emil Friis og Hustru Olga Doris Friis foundation in Denmark. All authors declare no competing interests. TRIAL REGISTRATION NUMBER: N/A